One Way FSI Study Of The Stress And Strain Distribution On The Water Dam Spillway Stilling Basin Baffles - Roslaili, Muhamad Zulhilmi (Universiti Sains Malaysia, 2018)
Baffle is a device used for altering the flow of water pattern. In a dam, baffle is very important as it is used to reduce the velocity of water in the spillway. In this study, the effect of geometry of baffles is investigated using computational simulation. By using four models of baffles the pattern of water stream flow is investigated. The flow pattern can be determined from water streamline and velocity contour of the stream flow. The static structural of maximum stress and strain of the baffles also is investigated. The static structural of maximum stress and strain can be obtained from the imported pressure of the simulation. From the simulation, the outlet velocity of water is also determined to check whether the results from simulation is same as the expected results. The results should have lower outlet velocity of water compared to inlet velocity of water. From the results, the best design of baffles is determined which has low outlet velocity of water and low static structural of maximum stress and strain.